(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study investigated if families’ healthy boundaries are related to late adolescents’ mental health. A survey with fundamental questions about mental health concerning a family’s healthy boundary and boundary protection was conducted haphazardly with 100 late adolescents. The survey questionnaire was disseminated using the online platform Google Forms. The analysis revealed that mental health concerning family healthy boundaries has a significant positive relationship with the protection boundary scale (r = 1, p.001). This implies that the lower the late adolescents’ boundary protection, the higher their boundaries with their families and mental health. The two scales indicate the level of protection provided by the individual’s self-boundary concerning the family’s healthy boundaries. The self-boundary is the line that separates and connects the individual and the environment. The findings suggest that researching other factors that may have influenced the results is highly appreciated.